2020
DOI: 10.1126/science.aax6752
|View full text |Cite
|
Sign up to set email alerts
|

Microglia monitor and protect neuronal function through specialized somatic purinergic junctions

Abstract: Microglia are the main immune cells in the brain and have roles in brain homeostasis and neurological diseases. Mechanisms underlying microglia–neuron communication remain elusive. Here, we identified an interaction site between neuronal cell bodies and microglial processes in mouse and human brain. Somatic microglia–neuron junctions have a specialized nanoarchitecture optimized for purinergic signaling. Activity of neuronal mitochondria was linked with microglial junction formation, which was induced rapidly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
486
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(520 citation statements)
references
References 66 publications
33
486
1
Order By: Relevance
“…In vitro cytotoxicity assays were made, to make preliminary assessment of toxicity, and to enable suitable concentration ranges to be used in future in vivo testing [64]. In this study, there was no statistically significant decrease in cell viability of human microglia treated with salamandrin-I as indicated by the resazurin assay up to 100 µM, suggesting an absence of cytotoxicity for this peptide ( Figure 6A).…”
Section: Toxicity Studiesmentioning
confidence: 76%
See 1 more Smart Citation
“…In vitro cytotoxicity assays were made, to make preliminary assessment of toxicity, and to enable suitable concentration ranges to be used in future in vivo testing [64]. In this study, there was no statistically significant decrease in cell viability of human microglia treated with salamandrin-I as indicated by the resazurin assay up to 100 µM, suggesting an absence of cytotoxicity for this peptide ( Figure 6A).…”
Section: Toxicity Studiesmentioning
confidence: 76%
“…In this study, there was no statistically significant decrease in cell viability of human microglia treated with salamandrin-I as indicated by the resazurin assay up to 100 µM, suggesting an absence of cytotoxicity for this peptide ( Figure 6A). Microglia are a type of glial cells located throughout the brain and spinal cord and account for 10%-15% of all glial cells found within the brain and constantly monitor neuronal functions through direct somatic contacts, and external neuroprotective effects [64]. In vitro non-cytotoxicity at high concentrations suggests the possibility of neuroprotective studies to assess whether the intrinsic antioxidant activity of the molecule can lead to cellular neuroprotection through regulation of microglia activity.…”
Section: Toxicity Studiesmentioning
confidence: 99%
“…However, multiple lines of evidence have suggested that microglia can regulate neuronal activity. For example, microglia were able to dampen neuronal hyperactivity under seizure context (Eyo et al, 2014;Kato et al, 2016) or even under physiological conditions (Peng et al, 2019;Cserep et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They can adopt different phenotypes, with environmentdependent transcriptional profiles (Gosselin et al, 2014(Gosselin et al, , 2017, and proinflammatory to pro-regenerative polarization (Miron and Franklin, 2014), though a strict dichotomy is an inadequate vision (Ransohoff, 2016). Microglial cells are further sensitive to neuronal activity Liu et al, 2019;Stowell et al, 2019;Cserép et al, 2020). Altered microglia activity at different stages of life is associated with developmental and acquired neurological pathologies and can impair the plasticity-related process and cognitive function (Morris et al, 2013).…”
Section: Control Of Myelination and Myelin Plasticity By Microgliamentioning
confidence: 99%